The Use of Red Dragon Fruit Gel as A Disclosing Agent for Plaque Measurement - RR Ratnasari Dyah Purnomowati; Arianto Arianto; Linasari Linasari; Muliadi Muliadi (Poltekkes Kemenkes Kupang, 2024)
Assessing oral hygiene through plaque index assessment is essential to identify areas that require attention, as poor hygiene can lead to problems such as caries, gingivitis, periodontitis and systemic health issues. In response to challenges such as limited access to natural tooth colouring materials and the side effects of chemical alternatives, red dragon fruit has emerged as a safe and natural option. This experimental study aimed to develop a red dragon fruit disclosing gel with concentrations of 35%, 50%, and 75% and to compare the staining effectiveness of these three concentrations. The study employed an experimental research design categorized as an